Cardiorespiratory Responses During High-Intensity Interval Training Prescribed by Rating of Perceived Exertion in Patients After Myocardial Infarction Enrolled in Early Outpatient Cardiac Rehabilitation - Dun, Yaoshan; Hammer, Shane M.; Smith, Joshua R.; MacGillivray, Mary C.; Simmons, Benjamin S.; Squires, Ray W.; Liu, Suixin; Olson, Thomas P. (Frontiers in Cardiovascular Medicine, 2022)
Objective: We aimed to determine the cardiorespiratory responses during, and adaptations to, high-intensity interval training (HIIT) prescribed using ratings of perceived exertion (RPE) in patients after myocardial infarction (MI) during early outpatient cardiac rehabilitation (CR). Methods: We prospectively recruited 29 MI patients after percutaneous coronary intervention who began CR within 2 weeks after hospital discharge. Eleven patients (seven men; four women; age: 61 ± 11 yrs) who completed ≥24 supervised HIIT sessions with metabolic gas exchange measured during HIIT once weekly for 8 weeks and performed pre- and post- CR cardiopulmonary exercise tests were included in the study. Each HIIT session consisted of 5–8 high-intensity intervals [HIIs, 1-min RPE 14–17 (Borg 6–20 scale)] and low-intensity intervals (LIIs, 4-min RPE < 12). Metabolic gas exchange, heart rate (HR), and blood pressure during HIIT were measured. Results: The mean oxygen uptake (V˙O2) during HIIs across 88 sessions of HIITs [91 (14)% of V˙O2peak, median (interquartile range, IQR)] was significantly higher than the lower limit of target V˙O2 zone (75% of V˙O2peak) recommended for the HII (p < 0.001). Exercise intensity during RPE-prescribed HIITs, determined as %V˙O2peak, was highly repeatable with intra-class correlations of 0.95 (95% CI 0.86– 0.99, p < 0.001). For cardiorespiratory adaptations from the first to the last session of HIIT, treadmill speed, treadmill grade, treadmill power, V˙O2HII, %V˙O2peak, and VE during HIIs were increased (all p < 0.05), while no difference was found for HR, %HRpeak and systolic blood pressure (all p > 0.05). V˙O2peak increased by an average of 9% from pre-CR to post-CR. No adverse events occurred. Conclusion: Our results demonstrate that HIIT can be effectively prescribed using RPE in MI patients during early outpatient CR. Participation in RPE-prescribed HIIT increases exercise workload and V˙O2 during exercise training without increased perception of effort or excessive increases in heart rate or blood pressure.